Flavoring Compounds in e-Liquids Identified by GC-MS: Chemical Insights and Respiratory Toxicity - Zulni, Shalsa Septia; Yuwono, Mochammad; Putri, Rury Eryna; Nabila, Aghnia; Fathoni, Rachmadi Azhar (Dinasti Research, 2025)
The use of e-cigarettes has surged as an alternative to conventional smoking, with e-liquids containing various flavoring chemicals that enhance user experience. However, these flavoring compounds may pose significant health risks when inhaled. This study systematically reviews the chemical composition of e-liquid flavorings identified using Gas Chromatography-Mass Spectrometry (GC-MS). A comprehensive literature review was conducted, sourcing articles from PubMed, Google Scholar, and ScienceDirect published within the last decade. The review focuses on identifying chemical compounds in various e-liquid flavors such as vanilla, bubble gum, coffee, tobacco, strawberry, lemon, and cannabis. Key compounds identified include vanillin, ethyl maltol, cinnamaldehyde, benzaldehyde, and limonene, which contribute to flavor profiles but may also have adverse respiratory effects. Thermal degradation of these compounds can result in the formation of harmful carbonyl compounds like formaldehyde and acetaldehyde, both classified as carcinogens. Furthermore, nicotine, a major component in e-liquids, increases the risk of addiction and psychological disorders. This review underscores the need for strict regulations on e-liquid flavoring agents and further research on the long-term effects of inhaling these substances. It also highlights the importance of public awareness regarding the potential respiratory toxicity associated with e-liquids and vaping.